Can psilocybin be safely administered under medical supervision? A systematic review of adverse event reporting in clinical trials. (March 2022) - Roscoe, Jeremy; Lozy, Olivia
This systematic review investigates whether clinical trials of psilocybin support criterion number three of the drug's schedule I designation: There is a lack of accepted safety for use of the drug or other substance under medical supervision . Data were collected by using the PubMed database and conducting a search on November 24, 2021, with the search term psilocybin and applying the clinical trial filter. Only primary reports on the sole administration of psilocybin by a medical professional were included for analysis, excluding trials wherein psilocybin was not administered, trials wherein psilocybin was exclusively co-administered with other drugs, articles that were not clinical trials, and articles that were repeat analyses of already included trials. 52 included publications were closely examined for reports of adverse events, drug tolerability, and drug safety. Zero of these articles reported psilocybin to be unsafe, while 27 of the included trials suggested that psilocybin is safe to administer under proper medical supervision.